Pembuatan Prototip Dye Sensitized Solar Cell (DSSC) Menggunakan Dye Ekstrak Buah Senduduk (Melastoma Malabathricum L) Dengan Variasi Fraksi Pelarut Dan Lama Perendaman Coating TiO2 - Fitria, Anisa; Amri, Amun; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Dye-Sensitized Solar Cell (DSSC) is a solar cell unit that work based on electrochemical principle which convert the sun radiation into electricity. DSSC uses TiO2 semiconductor material for coating with spin coating method. The purpose of this research is to make a DSSC prototype using of Malabar melastome fruit (Melastoma Malabathricum L.) as dye and also to observe the impact of water’s volume and soaking duration of TiO2 coating on the produced voltage. The DSSC is constructed with a layering system (sandwich) which consists of working electrode and counter electrode. The working electrode is made by using FTO glass (2.5 x 2.5 cm2) which is coated with TiO2 paste that made by mixing 0.5 gram TiO2 powder in 4 ml ethan ol (1:8). The electrode is sintered under temperature in 350oC for 15 minutes and then soaked in dye liquid with volume of solvent fraction in dye dilution which are ; without dilution (100%); diluted once (50%); and diluted twice (25%) for about 10 minutes, 2 hours and 24 hours. This electrode is then given two droplets of 0.05 M electrolyte. After that the counter electrode is made by using FTO glass coated with carbon from candle’s fire. The fabrication of DSSC is done by sticking both of the FTO glasses up. Melastome Malabar extract as dye is shown to contain anthocyanin, proven with a maximum wavelength of 515 nm. DSSC prototype generated by variation of 24 hours dye soaking duration and without dilution (100%) gave the highest voltage with the solar energy-to-electricity conversion of 1.026 volt/cm2 and when illuminated with LED lamp gave 0.595 volt/cm2. The morphology of TiO2 layer show a porous surface that is conducive to the absorption of dye. The level of adhesion obtained from the best samples showed good adhesion qualities (3B)Keywords: DSSC, LED, melastome malabar l, sunlight, voltage